Direction selectivity of neurons in the visual cortex is non‐linear and lamina‐dependent. (23rd March 2016) - Kim, Taekjun; Freeman, Ralph D.
Abstract: Neurons in the visual cortex are generally selective to direction of movement of a stimulus. Although models of this direction selectivity (DS) assume linearity, experimental data show stronger degrees of DS than those predicted by linear models. Our current study was intended to determine the degree of non‐linearity of the DS mechanism for cells within different laminae of the cat's primary visual cortex. To do this, we analysed cells in our database by using neurophysiological and histological approaches to quantify non‐linear components of DS in four principal cortical laminae (layers 2/3, 4, 5, and 6). We used a DS index (DSI) to quantify degrees of DS in our sample. Our results showed laminar differences. In layer 4, the main thalamic input region, most neurons were of the simple type and showed high DSI values. For complex cells in layer 4, there was a broad distribution of DSI values. Similar features were observed in layer 2/3, but complex cells were dominant. In deeper layers (5 and 6), DSI value distributions were characterized by clear peaks at high values. Independently of specific lamina, high DSI values were accompanied by narrow orientation tuning widths. Differences in orientation tuning for non‐preferred vs. preferred directions were smallest in layer 4 and largest in layer 6. These results are consistent with a non‐linear process of intra‐cortical inhibition that enhances DS by selective suppression of neuronal firing for non‐preferred directions of stimulus motion in a lamina‐dependent manner. Other potential mechanisms are also considered. Abstract : We have made a quantitative assessment of direction selectivity in visual cortex with a focus on laminar differences and questions concerning linearity. These three panels show spike discharge, reverse correlation maps, and Fourier derived spatiotemporal maps.